Genetic Recombination of the Mantle Color Pattern of Two Boring Giant Clam (Tridacna crocea) Strains - Wang, Junjie; Zhou, Zihua; Ma, Haitao; Li, Jun; Qin, Yanping; Wei, Jinkuan; Li, Xingyou; Liao, Qingliang; Li, Yunqing; Shi, Gongpengyang; Zhou, Yinyin; Zhang, Yuehuan; et al. (Frontiers in Marine Science, 2021)
According to the RGB law display, the polymorphism of the giant clam mantle color pattern is through four iridocytes. The boring giant clam (Tridacna crocea) exhibits diverse mantle colors, including blue, green, purple, gold, and orange. In order to evaluate the genetic laws driving these mantle color patterns, a complete diallel cross between two color strains [blue strain (only blue iridocyte) and the yellow-green strain (yellow and green iridocytes)] was performed. Using a single-to-single mating system, two intra-strain crosses (BB and YY) and two reciprocal inter-strain crosses (BY and YB) were produced in triplicates. Higher fertilization rate and hatching rate were observed in all experimental groups, suggesting that there was no sperm–egg recognition barrier between the two strains. In the grow-out stage, the size of the reciprocal hybrids was larger than that of the two pure strains with a degree of heterosis. In addition, compared with the two pure strains, the hybrids have higher larval metamorphosis rate and higher survival rate. At 1 year of age, the mantle color pattern of pure strains showed 100% stable inheritance, while the reciprocal hybrids exhibited colorful patterns (a combination of blue, yellow, and green), suggesting that there was a genetic recombination of the mantle colors during the stable expression period. These results provide a theoretical basis for the formation of the mantle color of giant clam and its genetic segregation law, as well as provide guidance for genetic breeding of giant clams.